Marble Waste Utilization in Geopolymerized Concrete Incorporating Outdoor Heat Exposure and Alkali Activated Material - Mohd Kusin, Faradiella (International Journal of Integrated Engineering, 2024)
Marble waste can be incorporated in the geopolymerized concrete production as supplementary cementitious material. Therefore, this study intends to assess physical and mechanical properties of a geopolymerized product through marble waste utilization under outdoor heat exposure (OHE) and use of alkali activated material (AAM). In the concrete production, marble waste was used at 20% by ratio and the specimen was subjected to OHE of 3-5 days and AAM/cement ratio of 0.3-0.4. Compressive strength analysis was performed to evaluate performance of geopolymerized concrete under the influence of OHE and AAM. The mineralogical and microstructure composition of the geopolymerized concrete were determined using XRD and SEM analysis, respectively. On average, specimens with 0.3-0.4 AAM/cement ratio and 3-5 days heat period have shown higher compressive strength than the control. The XRD and SEM analyses showed that the production of calcium silicate hydrate and other cementitious compounds were formed in the geopolymerized concrete product. Therefore, marble waste can be regarded as a suitable material to be used as supplementary cementitious material incorporating alkali activated material and outdoor heat exposure. This is in line with the concept of waste restoration in construction material for long-term environmental sustainability.